Exploring Philippines' preparedness to address early childhood care and development in emergencies - Sevilleno, Beverly F.; Agustin, Estrella R. (Quezon City College of Engineering, University of the Philippines Diliman, 2012)
The purpose of this study was to determine what has so far been achieved at the national level to ensure country preparedness in addressing the needs of younger children during disasters and emergency situations. In attempting to answer this question, this study responded to three objectives: First, identify researches on ECCD in Emergencies; second, identify policy to mainstream ECCD in Emergencies; third, identify programs and services to promote ECCD in Emergencies. Fifteen respondents representing eight National Government Agencies and seven Non- Government Organizations with national scope of work participated in this study. Face to face interview and survey were done to gather the data. Data revealed that only three researches related to ECCD in Emergencies have been conducted thus far in the Philippines. There are already existing national policy directives to create the necessary legal grounds for mainstreaming ECCD in emergencies. However, lacking still is the presence of clear cut policies directing all concerned sectors to develop and integrate disaster-related programs sensitive to the developmental needs of younger children. The programs and services that have been initiated by various national government agencies and non-government organizations can be classified according to the three phases of disaster: pre-disaster, during disaster, and recovery or rehabilitation. Interventions that would address the other aspects of early childhood such as protection, and programs for parents/primary caregivers of young children remain very limited. There may have already few researches, some policies and programs that can help address the needs of younger children during emergencies. Still, there is a long way to go in terms of preparedness in providing holistic and integrated programs and services to address the needs of young children in emergencies.
Thesis (MFLCD)--University of the Philippines Diliman.
Keywords: Children -- Philippines -- Services for; Emergency management -- Philippines